Severe fatigue due to valproate-induced hypothyroidism in a case of bipolar disorder - Tadashi Kanamori; Masahiro Suzuki; Yoshiyuki Kaneko; Kouju Yamada; Hideyuki Kubo; Makoto Uchiyama (Annals of General Psychiatry, 2020)
Abstract Background Valproate-induced hypothyroidism is a rare condition and has been considered asymptomatic. Here, we report a case of bipolar I disorder who developed symptomatic valproate-induced hypothyroidism. Case presentation A 44-year-old woman with bipolar I disorder complained of severe fatigue after starting valproate. She showed a hormonal pattern of central hypothyroidism. Thyroid autoantibodies were negative, and no pituitary abnormality was seen on magnetic resonance imaging. After stopping valproate, her severe fatigue rapidly improved with normalizing thyroid function. Conclusions Our case suggests that valproate-induced hypothyroidism should be considered when patients complain of excessive fatigue under treatment with valproate.